Probiotics mitigate thermal stress- and pathogen-driven impacts on coral skeleton - Moradi, Mahdi; Magalhaes, Phillipe R.; Peixoto, Raquel S.; Jonck, Cassia C.A.C.; François, Daniel; Bellot, Anna Clara F.; Teixeira, Jonatã B.; Silveira, Carla S.; Duarte, Gustavo; Evangelista, Heitor; Barbosa, Catia F. (Frontiers in Marine Science, 2023)
Threats leading to a reduction in coral populations are apparent worldwide. Several different approaches have been tested to accelerate the adaptation of corals to a changing climate. Here, we evaluated the skeletal structure, crystal habit, and chemical changes of the coral Pocillopora damicornis in response to pathogen (Vibrio coralliilyticus) and probiotic inoculation under ambient conditions (26 °C) and thermal stress (30 °C). Microtomography and energy-dispersive x-ray spectroscopy (EDX/SEM) were used to investigate the skeleto-physico-chemical micromorphological changes in porosity, pore size, bulk density, Mg/Ca, and Sr/Ca during the 50-day mesocosm experiments. The results indicate considerable changes in the coral skeleton caused by both temperature and microbial inoculation. Most importantly, lower density (to ~x̄ 0.5 g/cm 2 ) and higher porosity (up to ~ x̄ 47%) were correlated with inoculation of V. coralliilyticus and were mitigated by inoculation of probiotics (Beneficial Microorganisms for Corals, BMCs). BMCs also substantially increased calcification, as evidenced by Mg/Ca in the skeleton of thermally stressed corals. At micron scale, aragonite crystal fibers precipitated during the experiments showed an acicular habit in thermally stressed and pathogen-inoculated corals kept at 30 °C. In contrast, a This is a provisional file, not the final typeset article spherulitic habit, characteristic of high growth rates, was observed in corals inoculated with both BMCs and V. coralliilyticus. Our findings reveal that pathogen inoculation and thermal stress had notable impacts on coral skeleton properties including porosity, density, and crystal morphology in a short period of time, which highlights the potential impacts of shifts in climate warming and in environmental quality. On the other hand, BMC played a role in maintaining the properties of skeleton calcification.